PERBEDAAN KEMAMPUAN NATURALISTIK ANAK USIA 5-6 TAHUN MELALUI PEMANFAATAN LINGKUNGAN SEKOLAH DI TK YUZAI HARAPAN DESA SEI KOPAS - Esy Egidia Hutagalung; Wan Nova Listia (CV. ADIBA AISHA AMIRA, 2025)
The problems in this study are (1) The use of the environment is very minimal in the process of helping children learn, (2) Rarely utilizing real objects in the use of learning media, (3) Carrying out outdoor activities but teachers usually only focus on the development of gross motor skills. This study aims to see the differences in naturalistic intelligence in children aged 5-6 years using the use of the school environment at Yuzai Harapan Kindergarten, Sei Kopas Village. The method used in this study is an experiment, involving 36 children as samples. The tool used for data collection is using an observation sheet. Hypothesis testing with a paired sample T-test is preceded by a normality test carried out using the Shapiro Wilk statistical technique. The findings from the analysis of the hypothesis test of pretest and posttest data on children's naturalistic abilities produced data of 0.000. The data has a lower value compared to the significance level of 0.05, so it can be concluded that there is a significant difference between the pretest and posttest data related to the naturalistic abilities of children aged 5-6 years through the use of the school environment at Yuzai Harapan Kindergarten, Sei Kopas Village.